2022
DOI: 10.13057/biodiv/d230123
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Gyrinops versteegii from several agarwood plantation on Lombok Island (Indonesia) as raw material of Gyrinops tea

Abstract: Abstract. Wangiyana IGAS, Supriadi, Nikmatullah A, Sunarpi, Triandini IGAAH. 2021. Diversity of Gyrinops versteegii from several agarwood plantation on Lombok Island (Indonesia) as raw material of Gyrinops tea. Biodiversitas 23: 178-186. The purpose of this research is to examine the diversity of Gyrinops versteegii as a raw material of agarwood Gyrinops tea based on morphology, phytochemical, and molecular characters. G. versteegii samples were taken from 5 agarwood plantation on Lombok Island: Lingsar, Rarun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Barra (2009) explains that variations in secondary metabolite content in a plant species are influenced by three factors, namely (i) intraspecies genetic variation (ii) differences in plant organs and in the stages of plant organs development, (iii) differences in environmental factor. The effect of genetic variation within a species is in line with research conducted by Asensio et al (2020) and Wangiyana et al (2022). Asensio et al (2020) revealed that genetic and cytogenetic diversity (eg polyploidization) significantly affected the variations of phytochemical content in Bearberry.…”
Section: Study Region and Plant Materialssupporting
confidence: 72%
See 1 more Smart Citation
“…Barra (2009) explains that variations in secondary metabolite content in a plant species are influenced by three factors, namely (i) intraspecies genetic variation (ii) differences in plant organs and in the stages of plant organs development, (iii) differences in environmental factor. The effect of genetic variation within a species is in line with research conducted by Asensio et al (2020) and Wangiyana et al (2022). Asensio et al (2020) revealed that genetic and cytogenetic diversity (eg polyploidization) significantly affected the variations of phytochemical content in Bearberry.…”
Section: Study Region and Plant Materialssupporting
confidence: 72%
“…Asensio et al (2020) revealed that genetic and cytogenetic diversity (eg polyploidization) significantly affected the variations of phytochemical content in Bearberry. While Wangiyana et al (2022) reported that Molecular (genetic) variations in Gyrinops versteegii (Gilg.) Domke (Gyrinops tea) correlated with variations in phytochemical content and morphological variations between accessions.…”
Section: Study Region and Plant Materialsmentioning
confidence: 99%
“…These bands were treated as DNA fingerprinting characters for similarity value calculation. Similarity value was essential for clustering analysis for dendrogram construction (Wangiyana et al 2022). This systematic step has been used recently for genetic diversity studies based on microsatellite DNA fingerprinting (Driskill et al 2022;Fiore et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…RAPD markers can be recommended for use in Citrus breeding programs. To date, RAPD is still widely used to assess genetic diversity in various plant species [8,10,[32][33][34][35][36]. In Citrus plants, RAPD markers have been used for cultivar identifcation, mapping, genetic diversity assessment, and other breeding programs [37].…”
Section: Discussionmentioning
confidence: 99%